The Role of Finance Controlling in Mergers and Acquisitions - Korbutiak, Alina; Samsin, Ihor; Lokhanova, Natalia; Zhuk, Olena; Ustymenko, Olena (International Journal of Economics and Financial Issues, 2025)
The aim of the study is to analyse finance controlling as a key factor in case of mergers and acquisitions. It is also to evaluate the quantitative impact of finance controlling on the dynamics of merger and acquisition (M&A) transactions. The research employed the graphic method and cluster analysis to study the dynamics of the global M&A market. Regression analysis was also used to determine the impact of financial controlling and the companies’ M&A process. The results of the regression analysis, in particular the P-value, indicate the statistical significance of the influence of the predictor and confirm the relationship between finance controlling and the M&A market dynamics. In particular, the P-value for the number of transactions model is 0.0001, while for the value of transactions model — 0.0034, which indicates that there is no reason to reject the null hypothesis. This emphasizes the prospects for further study of the issue from a theoretical and practical perspective, in particular regarding the impact of internal controlling and the involvement of digitalization factors. Assessments of finance controlling in various industries and national economies are also important, which will give grounds to provide more reasonable recommendations for effective management in the current economic realities. Further research may focus on a deeper analysis of intra-company controlling and specific performance indicators. One of the areas of further research would be to analyse global statistics by country or economic sector.